Motivasi Belajar Pendidikan Jasmani Siswa Kelas X SMA Negeri 11 Semarang pada pembelajaran Teaching at The Right Level (TARL) - Yulvanto, One; Pradipta, Galih Dwi; Darmanto, Purno (Universitas PGRI Semarang, 2025)
This motivation includes the interest, need, and desire to master a material or skill. In the context of education, learning motivation plays an important role because it helps students to stay focused, disciplined, and persistent in facing learning challenges. The purpose of this study is to describe the motivation to learn physical education of Class X students of SMA Negeri 11 Semarang in Teaching at The Right Level (TARL) learning. This research uses a type of quantitative research with a survey approach to describe the learning motivation of class X students of SMA Negeri 11 Semarang in Teaching at The Right Level (TARL) learning. The data analysis technique is statistical descriptive with data collection techniques using questionnaires. The time and place of the research conducted in the research took place in the High School Class The instruments used in this study were observation guidelines and questionnaires. The learning motivation of students in class X of SMA Negeri 11 Semarang which is a very high group is 3 people or 6.98 percent, students with high motivation are 35 people or 81.40 percent, and students with medium motivation are 5 people or 11.63 percent. In addition, the average score was 55.53, the middle score was 56, the mode value was 57, the standard deviation value was 5.754, the minimum score was 43, the maximum score was 68, the number of respondents was 43 people and the total score was 2388.3.